Evalution of Antimicrobial Potential of Some Plants Against Pathogenic Bacteria - Narayanan Ganesh (International Journal of Phytomedicine, 2019)
uscuta reflexa, Orange peel, and Grapes were collected, authenticated, dried and powdered for the Maceration/Percolation process with different solvents. Pharmacognostical study of cuscuta (steam), orange (peel), and grapes (fruit) has been evaluated by using morphological, microscopical parameters. Phytochemical analysis of different extracts of identified the presence of alkaloid, terpenoids, glycosides, steroids, saponins, sterols, tannins and flavonoids and solubility test of different polar and non-polar solvent. In preliminary phytochemical evolution, different solvents systems were tried for developing a TLC system for phytochemical investigation of cuscuta reflexa orange peel, grapes. TLC study of these shows the presence of gallic acid and quercetin in Ethanolic extract of cuscuta reflexa at Rf value 0.68 and 0.75. Chloroform extract orange peel Rf value o.4 and 1, water extract grapes Rf value 0.8 and 1 shows the presence of phenolic and flavonoids compounds, which may be use for various pharmacological studies for the betterment of human life who ere suffering from different ailments. The study concludes that the all the three extracts (orange peel, cuscuta and grapes) exhibits antimicrobial activity against Gram positive and Gram negative bacterias